Natural content of heavy metals on cattle regions soils of Mayabeque and Artemisa province in Cuba - Amaral Sobrinho, N. M. B.; Febles Gonz?lez, J. M.; L?pez, Y. P.; Guedes, J. N.; Magalh?es, M. O. L.; Zoffoli, H. J. O. (Cuban Journal of Agricultural Science, 2013)
In order to determine the pseudo-total concentrations of heavy metals (HM) on Cuban cattle soils with established grasslands from Mayabeque and Artemisa provinces, and to propose reference values of quality, samples of eleven representative soils were collected. They were taken at two depths and the pseudo-total and phyto-availability contents of the HM were assessed. After a cluster analysis, the soils were distributed into four groups according to the similarities in the contents of Cu, Zn, Cd, Pb, Ni and Cr. A great variation of the natural values of HM in the different types of soils was demonstrated. Many of the values found are over those commonly reported in the international literature, especially those included in the third group, corresponding to ferralitic regions. Key words: degradation, trace elements, geochemical fund, values of reference.